Taurodontism of deciduous molars: Report of two cases - Srikanth Hanasoge Srivathsa (SRM Journal of Research in Dental Sciences, 2014)
Taurodontism, a disturbance of normal developmental of teeth where teeth lack normal constriction at the cervix with abnormally large rectangular tooth structure and pulp chambers. This anomaly can be noted in both permanent as well as deciduous dentition. In deciduous dentition, the prevalence is very low. This paper reports two cases of taurodontism in the deciduous dentition.